Effect of Dexmedetomidine on Posttraumatic Stress Disorder in Traumatic Brain Injury Patients Undergoing Emergency Craniotomy Surgery: A Retrospective Study - Yun-Qi Wang; Xian-Jie Zhang; Dan Zhou; Qing Li; Xin Liu (International Journal of Clinical Practice)
Conclusion: The use of DEX during anesthesia was effective in reducing the incidence of postoperative PTSD in TBI patients undergoing craniotomy.